Potential for Biofuels for Transport in Developing Countries - Kojima, Masami; Johnson, Todd (World Bank, Washington, DC, 2014)
Liquid biofuels made from biomass are attracting increasing interest worldwide. Industrial countries see biofuels as a way of reducing greenhouse gas (GHG) emissions from the transport sector and diversifying energy sources. Developing countries see biofuels as a way to stimulate rural development, create jobs, and save foreign exchange. Both groups view biofuels as a means of increasing energy security. These concerns, taken together and highlighted by recent surges in the world oil price, have prompted a wide range of countries to consider biofuels programs. Canada, Colombia, the European Union (EU), India, Thailand, and the United States have adopted new targets, some mandatory, for increasing the contribution of biofuels to their transport fuel supplies. In Brazil, after a period of a decline in ethanol consumption, flex-fuel vehicles-capable of running on varying percentages of ethanol-are revitalizing the ethanol market.